Fuzzy Logic-based Integrated Cooling System to Improve PV Efficiency - Dinata, Seflahir; Mohamad Ayob, Ahmad Faisal; Albani, Aliashim; Cristian, Raynaldi; Ardianto, Donie Agus; Rozak, Ojak Abdul (LPPM Universitas Andalas, 2023)
Photovoltaic (PV) temperature is an important parameter that can influence PV performance. The increase in PV temperature can cause a drop in PV output voltage, which indicates that the PV does not operate optimally. In this paper, a design of an integrated cooling system based on fuzzy logic to control the PV temperature is presented. This, in effect, will potentially ensure that the PV performance is at its maximum condition. In this work, the temperature of the PV is kept constant by attaching a cooling system that carries water inside it. The constant temperature of the cooling system is carried out through a radiator and thermoelectric with electronic control. The experiments are carried out using two 320-watt PV systems; one with the cooling mechanism and the latter without the cooling system as a control. Several important data such as temperature, voltage, current, and radiation measurement in each PV were collected for three days from 10:00 to 17:00 with an interval of 10 minutes for each measurement. The results of the integrated cooling system measurement showed an increase in PV power generation and efficiency of 1.32% compared to the control PV unit. From the results of the study, it can be concluded that the fuzzy logic-controlled cooling system contributed to the increase in PV performance.